Reducing Postoperative Pain Following Turp in Patients with Benign Prostatic Hyperplasia (BPH) - Rudi Hartono; Wahyu Endang Setyowati; Dwi Retno Sulistyaningsih; Indah Sri Wahyuningsih (GLOBAL HEALTH SCIENCE GROUP, 2026)
Benign Prostatic Hyperplasia (BPH) is common in men and worsens with age. Transurethral Resection of the Prostate (TURP) is a common treatment but may cause post-operative pain. Non-pharmacological interventions such as warm and cold compresses are often used to reduce pain. Data from KHZ Musthafa Regional Hospital, Tasikmalaya Regency, recorded 302 BPH cases between April and June. This study aimed to compare the effectiveness of warm and cold compresses in reducing post-operative pain in TURP patients. A quasi-experimental pretest-posttest control group design was used. The population consisted of 101 TURP patients over three months. Purposive sampling selected 60 participants, divided into Group 1 (warm compress, n = 30) and Group 2 (cold compress, n = 30). Warm compresses were applied using a hot water bottle, and cold compresses using ice water; temperatures were monitored with a thermometer. Pain was measured using the Numerical Rating Scale (NRS) before and after intervention. Data were analyzed using central tendency, paired t-tests, and independent sample t-tests. Participants were aged 61–70 years, mostly with junior or senior high school education, and worked in private sectors or as employees. Warm compresses reduced pain from 5.53 (moderate) to 3.07 (mild), and cold compresses from 5.63 to 3.90. Both interventions significantly reduced pain (p = 0.000), with warm compresses more effective than cold (p = 0.003). Warm compresses are more effective than cold compresses in reducing post-TURP pain, though both significantly decrease pain levels.